STUDI LITERATUR: HUBUNGAN DISIPLIN BELAJAR DENGAN HASIL BELAJAR MATA PELAJARAN IPS SISWA SEKOLAH DASAR - Meazza Ratry Aryaningrum; Suntri, Yustia; Dallion E.W, Engga (Jurnal Dikdas Bantara, 2024)
Discipline plays an important role in shaping student behavior, work ethic, and overall academic success. Learning discipline and learning outcomes have a very close correlation for several reasons. This study aims to review the literature related to the problem on the relationship between learning discipline and learning outcomes of social studies subjects of  elementary school students. The type of data used is secondary data. The method to be used in this research is literature study. The data obtained is compiled, analyzed, and concluded so as to get a conclusion about the literature study. Based on the results of the literature study, it shows that there is a significant relationship between learning discipline and learning outcomes of social studies subjects in elementary school students. Learning discipline, such as accuracy and thoroughness in doing assignments, learning time management, and paying attention to lessons, greatly affects the improvement of student learning outcomes. Conversely, indiscipline, such as lack of time management, being late or not doing assignments, and not paying attention to lessons, can result in a decrease in student learning outcomes.